Penguatan Literasi Digital bagi Guru Bimbingan Konseling melalui Aplikasi Berbasis Web Digitalliteracy.id di Kabupaten Sleman - Reno Sugiarto; Miko Yuristiawan; Didik Haryadi Santoso (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
This program aims to improve the digital literacy of Guidance and Counseling (BK) teachers at SMA/SMK/equivalent in Sleman Regency through the development of a web-based application digitalliteracy.id. This program is implemented in collaboration with the Consultation of Guidance and Counseling Teachers (MGBK) as an effort to increase the understanding of new media literacy among educators. The implementation method included three main stages: (1) socialization to introduce the concept of digital literacy, (2) intensive training in the use of the application, and (3) mentoring to ensure program sustainability. The application development adopted the Software Development Life Cycle (SDLC) method with systematic stages, including needs analysis, interface design, feature development, functionality testing, implementation, and post-launch evaluation. This application is designed to assist counseling teachers in identifying students' digital literacy problems, providing interactive materials, and facilitating technology-based counseling. Evaluation results show significant improvements in teachers' ability to integrate digital media into counseling services, as well as increased work efficiency through the automation of some guidance processes. The long-term impact of the program includes strengthening the role of counseling teachers in educating students about digital safety and ethics. Thus, digitalliteracy.id is not only a technical tool, but also encourages digital transformation in the education environment.